Qualidade hospedeira e preferência de Lysiphlebus testaceipes (Cresson) (hymenoptera: braconidae) por diferentes ínstares de Schizaphis graminum (Rondani) (hemiptera: aphididae) - Vieira, Lorrayne Jacinto Pacheco (2018)
The parasitoid Lysiphlebus testaceipes (Cresson) (Hymenoptera: Braconidae) is an important biological control agent parasitizing several aphid species, such as Schizaphis graminum (Rondani). Studies involving the preference and quality of host aphids species can provide important information regarding the mass rearing, conservation and use of parasitoids as biological control agents. Thus, the objective of this work was to determine the relationship between the preference of the parasitoid and the host quality of different instars of S. graminum for L. testaceipes. To this end, S. graminum aphids were collected and transferred to Petri dishes with sorghum leaves fixed in 1% agar-water and kept in a climatic chamber with a temperature of 23 ± 1 ° C and a photophase of 12 h, until a formation of second and fourth instar nymphs, which were used in the experiments. The choice test was performed with a parasitoid foraging arena containing 20 nymphs (ten of each instar) and the non-choice test 10 nymphs of the same instar, both testes with 15 repetitions. One female of L. testaceipes was released in the arena and observed for 5 min under a stereoscopic microscope. Were evaluated the number of encounters, the number of parasitoid probes with the ovipositors and the number of ovipositions. After the observations, the aphids of the choice test were kept in a climatic chamber at 23ºC for three days and then dissected to evaluate the number of larvae of the parasitoids inside the aphids. On the other hand, the aphids of the non-choice test were kept in the climatic chamber until the complete development of the parasitoid and were evaluate the developmental time, the size of the hind tibia and the number of eggs in the female ovarioles (egg load). In the choice test there were more encounters and ovipositions of the parasitoid on the fourth instar aphids and this instar showed a bigger number of aphids with larva of the parasitoid inside. In the non-choice test the number of oviposition and the number of eggs in the ovarioles were larger and the development time of the parasitoid was shorter when emerged from fourth instar nymphs. Thus, it is concluded that the fourth instar of S. graminum is preferred by L. testaceipes and presents higher host quality than the second instar, due to the shorter development time and greater reproductive potential and size of the parasitoid.